Pre-processing importance for extracting contours from noisy echocardiographic images - Hussein, Zinah Rajab; O. K. Rahmat, Rahmita Wirza; Abdullah, Lili Nurliyana; Saripan, M. Iqbal; Dimon, Mohd Zamrin (IJCSNS, 2009)
Contours extraction from two dimensional echocardiographic images has been a challenge in digital image processing. This is essentially due to the heavy noise, poor quality of these images and some artifacts like papillary muscles, intra-cavity structures as chordate, and valves that can interfere with the endocardial border tracking. In this paper, we will present a technique to extract the contours of heart boundaries from a sequence of echocardiographic images, where it started with pre-processing to reduce noise and produce better image quality. By pre-processing the images, the unclear edges are avoided, and we can get an accurate detection of both heart boundary and movement of heart valves.